2015
DOI: 10.1080/10826076.2015.1037451
|View full text |Cite
|
Sign up to set email alerts
|

Study on the HPLC Chromatograms and Pro-Angiogenesis Activities of the Flowers ofPanax notoginseng

Abstract: Panax notoginseng is often used to promote blood circulation for the intervention of cardiovascular diseases (CVDs), while the flower of Panax notoginseng (PF) is used in folk remedies for the amelioration of hypertension in the Yunnan Province of China as a tea and is increasing in popularity throughout Asia. Previous studies on the Panax notoginseng were mainly focused on the root such that limited research on the flower cannot feed the need of increasing consumption and the products quality and pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Angiogenesis could also be an indicator of many diseases including wound healing, the menstrual cycle, cancer, various ischemic and inflammatory diseases, and even infarcted myocardium [24, 25]. Our previous study demonstrated that flowers of Panax notoginseng had proangiogenic effects on healthy and vessel-lost zebrafish which were damaged by VEGF receptor kinase inhibitor [26]. Intriguingly, our findings also indicated that purified saponin preparation from flowers of Panax notoginseng had more powerful and significant angiogenic/restorative effects than the extract from roots of Panax notoginseng [15, 1719].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis could also be an indicator of many diseases including wound healing, the menstrual cycle, cancer, various ischemic and inflammatory diseases, and even infarcted myocardium [24, 25]. Our previous study demonstrated that flowers of Panax notoginseng had proangiogenic effects on healthy and vessel-lost zebrafish which were damaged by VEGF receptor kinase inhibitor [26]. Intriguingly, our findings also indicated that purified saponin preparation from flowers of Panax notoginseng had more powerful and significant angiogenic/restorative effects than the extract from roots of Panax notoginseng [15, 1719].…”
Section: Discussionmentioning
confidence: 99%
“…Total saponins from both notoginseng roots and notoginseng flower buds are reported to be pro-angiogenic (Hong et al, 2009;Yang et al, 2016a), while notoginseng buds have better pronounced protective effect against intersegmental blood vessels (ISVs) and subintestinal vessels (SIVs) than Panax ginseng roots when concentration is 50 g/mL (Zhang et al, 2013). In addition, natural compounds, including notoginsenoside R1 and ginsenoside Rb1, Rb3, F1, Re, and Rg1 are reported to increase the intensity of fluorescent blood vessels in the VRIinduced zebrafish, indicating their potential to promote angiogenesis (Xie et al, 2015;Yang et al, 2016b;Zhang et al, 2019;.…”
Section: Zebrafish As a Promising Model For Investigating Biological ...mentioning
confidence: 99%
“…The transgenic lines of Tg (fli1a: EGFP) and Tg (Flk1: GFP) mark vascular endothelial cell-relevant proteins that drive green fluorescence and are often used to study angiogenesis and vascular regression, as displayed in Table 2. Numerous studies have utilized the vascular endothelial growth factor (VEGF) receptor tyrosine kinase inhibitor II (VRI) to induce arterial damage in these transgenic zebrafish, which significantly attenuate the intensity of fluorescence of blood vessels (Xie et al, 2015;Yang et al, 2016a). Based on such a model, red ginseng extracts are reported with pro-angiogenic effect on blood vessel sections of zebrafish larvae (Sung et al, 2017).…”
Section: Zebrafish As a Promising Model For Investigating Biological ...mentioning
confidence: 99%
“…The restraint of delta-like 4 (DII4)-Notch by fortification of microRNA-30a (miR-30a) can prompt angiogenesis in zebrafish [65]. The flowers of Panax notoginseng were found to be able to repair the damaged blood vessels by accelerating angiogenesis in zebrafish embryos [73]. This plant is utilised as a part of traditional Chinese medicine for the treatment of hypertension [72].…”
Section: Zebrafish As a Model To Studymetabolic Syndromementioning
confidence: 99%